Phonological Rules In English :Analysis Of Application By Uinsu English Tadris Students - Tambunan, Nurul Fadilah; Anissa; Harshanda Rafika Putri; Yani Lubis (PT Rahis Cendekia Indonesia, 2025)
Phonology is a linguistic branch that studies the sound system in a language. In English, phonological rules are very important to understand so that pronunciation and understanding of meaning do not experience distortion. However, for English learners as a foreign language (EFL), including English tadris students in north Sumatra UIN (UINSU), the appclication of phonological rules is often a challenge. This is caused by differences in the sound system between Indonesian and English and lack of exposure to native speakers.This article aims to analyze the extent to which UINSU English Tadris students understand and apply phonological rules in English, and identify common mistakes that occur